Lithogeochemistry Of "Exhalites" Associated With Massive Sulfides And Their Origin As Fallout From Hydrothermal Plumes (International Marine Minerals Society, 1993)
Ancient volcanogenic Cu-Zn-Pb-Ag-Au massive sulfide ores commonly have associated with them along strike and in the immediate hanging wall a distinctive sediment that is thin, usually cherty and metal enriched, and generally referred to as an "exhalite horizon" or "tuffaceous exhalite". Typical examplks include the 13 Ma tetsusekiei of the Kuroko deposits of Japan (Kalogeropoulos and Scott, 1983, Econ. Geol.) and the 2700 Ma contact tuffs of Noranda, Canada (Kalogeropoulos and Scott, 1989, Can. J. Earth Sci.) and Key Tuffite of Mattagami, Canada (Liaghat and McLean, 1992, Explor. Min. Geol.). Attempts to use trace element distributions as lithogeochemical guides to ore have been largely unsuccessful. Exhalites have been considered to be the products of seafloor hydrothermal activity that is peripheral to the main ore-producing vents. However, large actively-forming polyrnetallic sulfide deposits at the Explorer mid-ocean basalt spreading ridge (1 850 m depth) in the NE Pacific and the eastern Manus back-arc dacitic spreading center (1650 m depth) in the western Pacific have demonstrated that the exhalite horizons are more likely produced by fallout of particulates from the main hydrothermal plume. In a typical hydrothermal plume, grains of >27 µm represent up to 97% of the mass (although only 2% of the population) of the particulates and are calculated by Stokes equations to fall from the plume to the seafloor within a few krn of their source. The particles are primarily composed of anhydrite, barite, amorphous silica, iron oxyhydroxides and metal sulfides and oxides. Plumes are subject to bottom currents which push them in preferred directions, just like smoke plumes in the atmosphere are subject to the vagaries of wind direction. Bottom currents in the deep ocean can be 50 m/min or